Effect of Sintering Temperature on Mechanical Properties and Microstructure of Sheep-bone Derived Hydroxyapatite (SHA) - (:unkn) unknown (My University, 2009)
Hydroxyapatite (HA) is currently one of the most attractive materials for human hard tissue implants because its close crystallographic resemblance to bones and teeth, conferring HA with excellent biocompatibility. Because of that fact as well as economic and time-saving reasons, we have stressed the need for safe production of HA-powders and ceramics from natural resources, such as animals' bones and teeth, or hydrothermal transformation of shell's aragonite. Nevertheless, the applications of pure HA-ceramics are limited to non load-bearing implants, because of HA's poor mechanical properties. Our research group has dedicated a lot of effort to achieve enhancement of mechanical strength and the fracture toughness of sintered HA-ceramics, mainly with HApowder of natural origin, by fabricating composite materials of HA doped with various types of biocompatible oxides. This work aims to present that bulk ceramics of pure HA (i.e. with no incorporation of any reinforcing phase), derived from sintered HA-powder obtained from calcinated (at 850°C) bones of sheep (SHA), exhibit the best mechanical properties ever measured for sintered HA ceramics (pure and composites) using naturally (i.e. animal bone) derived HA. The characterization of the new HA-ceramics comprised measurements of density and mechanical properties, namely compressive strength and Vickers microhardness, along with microstructure observation with scanning electron microscopy (SEM). The best mechanical properties were achieved in the samples sintered between 1200°C-1300°C; the highest value of compression strength was achieved after sintering at 1300°C, 180.75 MPa. SEM observations in conjunction with density measurements confirmed the good sintering ability of the SHA-powders to highly condense bulk HA-ceramics.
Keywords: Hydroxyapatite; mechanical properties; sheep derived hydroxyapatite